DETERMINANTS ASSOCIATED WITH BLOOD LIPID LEVEL AMONG UNIVERSITY STUDENTS AND STAFF IN THAILAND - Tohma, Yareeyah; Bueto, Nursaneeta; Kumar, Suresh; Kumari, Reya; Naeem, Nawal; Ethisan, Plernta (Journal of Ayub Medical College Abbottabad, 2025)
Background: Noncommunicable Diseases (NCDs) are considered as major public health threats and contributes a high burden of diseases on health system of Thailand. Around 74% of deaths occur due to NCDs, and more than 40,000 people die annually in Thailand due to this problem. Objectives of the study were to know the blood lipid level and its determinants among university students and employees of Thailand. Methods: This study was cross-sectional to determine the relationship between various factors with blood lipid level among university students and employees. A total 219 participants were invited and included randomly in this study. Only those respondents who had their lipid profile checked recently during one of time were included and those who had other associated diseases were excluded in this study. Chi-square and Binary logistic regression were used to assess the factors associating with blood lipid level among the study participants. Study was ethically approved from the ethical review board of university and written consent was taken prior to start the data collection. Results: Total 219 respondents were included in this study, majority 84% were females. The mean age of participants was 26.18 (SD±9.81) years. About three-fifth (63%) had normal blood lipids, when we considering those with abnormal blood lipids, it was found that the sample group had the most abnormal cholesterol 37.44% and LDL 28.77%. Study found that only the variable of age was statistically significant in bivariate analysis. By people aged 26 and over had abnormal blood lipid 2.953 times more than those age 20-25 years. The income variable was found to have no relationship with blood lipid status at p>0.05. Conclusion: This study concludes that the university students and employees are on high risk to develop the cardiac diseases and the factor like age has a greater impact on abnormal blood lipids.